2018
DOI: 10.1371/journal.pone.0202118
|View full text |Cite
|
Sign up to set email alerts
|

Alginate encapsulated multipotent adult progenitor cells promote corneal stromal cell activation via release of soluble factors

Abstract: To reduce the increasing need for corneal transplantation, attempts are currently aiming to restore corneal clarity, one potent source of cells are multipotent adult progenitor cells (MAPC®). These cells release a powerful cocktail of paracrine factors that can guide wound healing and tissue regeneration. However, their role in corneal regeneration has been overlooked. Thus, we sought to explore the potential of combining the cytoprotective storage feature of alginate, with MAPC to generate a storable cell-lad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…These are characteristic of living organisms and also many complex materials such as polymers and colloids. Relevant active research in the UK encompasses the fields of medicine (Ma et al, 2016;Burton et al, 2019;Coudrillier et al, 2016;Al-Jaibaji et al, 2018;Kudsiova et al, 2019), biology (Troilo et al, 2016;McGeehan et al, 2011;Arnold et al, 2011;Salamah et al, 2018), the environment (Neill et al, 2018;Seddon et al, 2016) and materials (Summerton et al, 2019;Wychowaniec et al, 2018;Burton et al, 2017), and includes studies of supramolecular organization in biomechanical systems (Xi et al, 2018;Kampourakis et al, 2018;Sui et al, 2014), corneal transparency (Morgan et al, 2018;Hayes et al, 2017), biological membranes (Barriga et al, 2016;Slatter et al, 2018;, polymer processing (Stasiak et al, 2015;Wan et al, 2018;Heeley et al, 2013;Toolan et al, 2017), colloids (Calabrese et al, 2019;Poulos et al, 2016;Mable et al, 2016), inorganic aggregates (Raine et al, 2018;Bennett et al, 2015;Zhou et al, 2018), liquid crystals (Hallett et al, 2014;Prehm et al, 2018;Lehmann et al, 2018) and devices (Xia et al, 2018;Barrows et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These are characteristic of living organisms and also many complex materials such as polymers and colloids. Relevant active research in the UK encompasses the fields of medicine (Ma et al, 2016;Burton et al, 2019;Coudrillier et al, 2016;Al-Jaibaji et al, 2018;Kudsiova et al, 2019), biology (Troilo et al, 2016;McGeehan et al, 2011;Arnold et al, 2011;Salamah et al, 2018), the environment (Neill et al, 2018;Seddon et al, 2016) and materials (Summerton et al, 2019;Wychowaniec et al, 2018;Burton et al, 2017), and includes studies of supramolecular organization in biomechanical systems (Xi et al, 2018;Kampourakis et al, 2018;Sui et al, 2014), corneal transparency (Morgan et al, 2018;Hayes et al, 2017), biological membranes (Barriga et al, 2016;Slatter et al, 2018;, polymer processing (Stasiak et al, 2015;Wan et al, 2018;Heeley et al, 2013;Toolan et al, 2017), colloids (Calabrese et al, 2019;Poulos et al, 2016;Mable et al, 2016), inorganic aggregates (Raine et al, 2018;Bennett et al, 2015;Zhou et al, 2018), liquid crystals (Hallett et al, 2014;Prehm et al, 2018;Lehmann et al, 2018) and devices (Xia et al, 2018;Barrows et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that alginate gels are suitable for storage and transport of immobilised embryonic stem cells, limbal epithelial stem cells, mesenchymal stem cells, and multipotent adult progenitor cells [ 28 , 29 , 45 , 46 ], proving that alginate is able to protect cells phenotype. Comparable with literature, Ad-MSCs bandages stored at 15 °C showed optimum cell recovery and a similar immunophenotype marker expression where they had low expressions of major histocompatibility class II (MHCII) and absence of CD45 and CD14, while expressing CD90 and CD73, thus proving the suitability of our encapsulation method and the functionality of alginate in maintaining the encapsulated cells progenitor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In 1 mL sodium alginate, 2 × 10 6 viable cells were encapsulated using a BeadReady™ kit (Atelerix, Newcastle Upon Tyne, UK) with a modified protocol. Briefly, 2× concentrated sodium alginate +/− cells were mixed with SFM before casting in ring-shaped filter papers soaked with the supplied gelation buffer for initial gelation of 2 min followed by 6 min incubation in gelation buffer at room temperature as described previously [ 45 ]. The formed alginate rings +/− cells were then stored at 15 °C for 72 h before use in in vitro or in vivo wound healing studies.…”
Section: Methodsmentioning
confidence: 99%
“…Dental pulp stem cells Poloxamer 407 [28] Human placenta-derived mesenchymal stem cells Alginate [31] Multipotent adult progenitor cells Alginate [52] Mouse embryonic stem cells PEG-fibrinogen [38] AOLA Encapsulation technology has greatly advanced due to the parallel advancement of material and microfluidics science, giving rise to microencapsulation that can allow even single-cell encapsulation [58], thus practically giving the opportunity to "dress up" individually the stem cells depending on the application.…”
Section: Stem Cell Type Biomaterialsmentioning
confidence: 99%
“…Nonetheless, alginate alone seems to have some positive effects, depending on the application. For instance, Al-Jaibaji et al showed that the encapsulation of multipotent adult progenitor cells in alginate hydrogels could induce a wound-healing reaction in corneal stromal cells, through the secretion of soluble factors by the progenitor cells [52].…”
Section: Alginatementioning
confidence: 99%